Analyzing online comments: a language-awareness approach to cultivating digital literacies. Issue 4 (3rd May 2020) - Chen, Cheryl Wei-Yu
Abstract: The advent of technology has made the Internet a fertile ground for much literacy learning to take place, and how to use the Internet discourse for language learning remains to be explored. The current study adopted a language-awareness approach to raise students' awareness of the forms and function of online language. A sample online comment thread was prepared to lead the participants to begin to observe and analyze online language before they collected their online comments to build their personal portfolios. It was found that the participants mainly resorted to Facebook (58.0%) and YouTube (35.8%) to find comments; 69.1% of their topics were related to news stories while the remaining can be categorized as entertainment and personal interests. Students reported to have learned the importance of taking responsibility for one's words online. In terms of knowledge, many students gained new knowledge about slang and world issues. They also felt that learning to read and evaluate online comments was an enjoyable and empowering experience. This study concludes with a few suggestions for future research to further investigate the potential benefits of incorporating online comments into language pedagogy.